Evaluasi Usability Aplikasi Mobile Banking Menggunakan Metode Retrospective Think Aloud dan Post-Study System Usability Questionnaire - Naufal, Muhammad; Ahsyar, Tengku Khairil; Jazman, Muhammad; Permana, Inggih (AI Society & STMIK Indonesia, 2024)
BRKS Mobile is a digital service provided by Bank Riau Kepri Syariah to facilitate its customers in conducting financial transactions via smartphones. Because this application is relatively new, there are problems when running the application. The results of user reviews on playstore comments and pre-surveys, the problem that often occurs is errors when making transactions. In this study, usability evaluation was carried out using the Retrospective Think Aloud (RTA) and Post-Study System Usability Quesionaire (PSSUQ) methods. The results of the usability measurement show that users experience little difficulty when running the transfer and purchase menus. This is reinforced by the results contained in the norms of the PSSUQ method where the results of the SyeUse variable value of 2.70 and InfoQual 2.95 are below the average which indicates that the usability of the system and the quality of information on BRKS Mobile are still lacking. For the InterQual value of 3.09, it is above average and overall the BRKS application is at 2.89 above average, which means that the application can be accepted by its users.